Dispersão salarial em economias desenvolvdas e em desenvolvmento: uma análise da validade das predições do modelo Heckscher-Ohlin-Samuelson - SOUZA JÚNIOR, Raimundo Borges de (2024)
The increase in wage dispersion observed between skilled and unskilled workers in the United States coincided with the process of trade liberalization (globalization) that began in the 1980s. This coincidence led economists to study the relationship between the two phenomena, since the increase in wage dispersion has also been recorded in other countries. The theories most used to explain the effects of globalization on wage dispersion between skilled and unskilled workers are based on the Heckscher-Ohlin (HO) model, the Stolper-Samuelson (SS) theorem or the Heckscher-Ohlin-Samuelson (HOS) model. Since the 1980’s and 1990’s, empirical studies have not been unanimous in confirming the predictions of the HOS model, especially with regard to developing countries. This systematic review examined the effects of globalization on wage dispersion in developed and developing countries in light of the HOS model. The results suggest that wage dispersion increased in both groups of countries, confirming the model’s predictions for developed countries, but contradicting the predictions for developing countries.